Training, Self-Efficacy, and Work Motivation: A Conceptual Model of Employee Performance - Endang Pujiastuti (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: The background shows that training does not always result in improved performance if it is not accompanied by supporting psychological mechanisms, so a more integrative framework is needed to understand the relationship between variables. Objective: This study aims to develop a conceptual model that explains the contribution of training and development and self-efficacy to employee performance through work motivation mediation. Methods: This study uses the library research method by examining academic literature, journal articles, and relevant scientific publications in the last ten years to identify consistent theoretical patterns and empirical findings. Results: The results of the synthesis show that training and development function as a job resource that strengthens competence, job readiness, and perception of organizational support, while self-efficacy acts as a personal resource that increases self-confidence, perseverance, and achievement orientation. Both resources encourage work motivation as a key psychological mechanism that translates capacity building and self-confidence into optimal work behavior and higher performance. The integration of Social Cognitive Theory and Job Demands–Resources Model in this model provides a more comprehensive explanation of the psychological pathway of HR development interventions. Conclusion: In practical terms, these findings confirm the importance of training design that focuses not only on technical skills, but also on strengthening self-efficacy and work motivation to have a more effective impact on performance.